2021
DOI: 10.1038/s41598-021-94773-6
|View full text |Cite
|
Sign up to set email alerts
|

Expression of HO1 and PER2 can predict the incidence of delirium in trauma patients with concomitant brain injury

Abstract: Intensive care unit (ICU)-acquired delirium is associated with adverse outcome in trauma patients with concomitant traumatic brain injury (TBI), but diagnosis remains challenging. Quantifying circadian disruption by analyzing expression of the circadian gene period circadian regulator 2 (PER2) and heme oxygenase 1 (HO1), which determines heme turnover, may prove to be potential diagnostic tools. Expression of PER2 and HO1 was quantified using qPCR from blood samples 1 day and 7 days after trauma. Association a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…4–6 In aged mice subjected to ASI, sleep was interrupted by frequent arousals, awake EEG activity was characterized by loss of high frequencies, and awake EEG slowing was strongly correlated with behavioral quiescence. In addition, ASI mice failed to synchronize their sleep-wake activity with external light cues, and their expression of key molecular components of the brain circadian clock 22–27 was decreased relative to controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4–6 In aged mice subjected to ASI, sleep was interrupted by frequent arousals, awake EEG activity was characterized by loss of high frequencies, and awake EEG slowing was strongly correlated with behavioral quiescence. In addition, ASI mice failed to synchronize their sleep-wake activity with external light cues, and their expression of key molecular components of the brain circadian clock 22–27 was decreased relative to controls.…”
Section: Discussionmentioning
confidence: 99%
“…Given their inability to align their sleep-wake state with light cues, we next asked whether the expression of core clock genes necessary for normal circadian function was impaired in ASI mice. [22][23][24][25][26][27] Brains were collected at the same time for all animals at the end of simulated ICU conditions. Indeed, we found that mRNA levels of CLOCK, BMAL1, PER1, PER2, PER3, www.anesthesia-analgesia.org 217 CRY1, and CRY2 genes were significantly decreased in ASI mice relative to controls (BMAL1: −1.3-fold; CLOCK: −1.2; CRY1: −1.4; CRY2: −1.2; PER1: −1.2; PER2: −1.4; and PER3: −1.3; Figure 7A).…”
Section: Asi Impair Circadian Function In Aged Micementioning
confidence: 99%
“…Delirium, an acute mental state change, is characterized by inattention, arousal disorders and mental disorders [ 28 ]. However, the presence of delirium caused irreversible damage to the brain function of patients, significantly increased the total length of hospital stay, significantly increased the cost of hospitalization, and even seriously affected the prognosis [ 28 , 29 ]. Delirium is highly common in patients with severe TBI and can occur at any time during a patient's hospital stay, and studies suggest that up to 70% of patients present during a hospital stay [ 28 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although clinical scoring systems have been around for many years, in the last few years, novel laboratory markers have been shown to predict those at highest risk for delirium among trauma patients. In a small study, Steimer et al [30 ▪ ] in 2021 showed that expression of circadian gene period regulators (PER2) and heme oxygenase 1 (HO1) early in the hospital stay in trauma patients correlated with development of delirium in an age-independent fashion. With more widespread use and availability, biomarkers like these may serve as useful predictors allowing more targeted assessment and prevention.…”
Section: Elderly Patients With Rib Fracturesmentioning
confidence: 99%